2022
DOI: 10.1080/15384047.2022.2054249
|View full text |Cite
|
Sign up to set email alerts
|

Graphene quantum dots mediated magnetic chitosan drug delivery nanosystems for targeting synergistic photothermal-chemotherapy of hepatocellular carcinoma

Abstract: Conventional clinical monotherapies for advanced hepatocellular carcinoma (HCC) have numerous limitations. Integrated oncology approaches can improve cancer treatment efficacy, and photothermal-chemotherapy drug delivery nanosystems (DDS) based on nanotechnology and biotechnology have piqued the interest of researchers. This study developed an aptamer-modified graphene quantum dots (GQDs)/magnetic chitosan DDS for photothermal-chemotherapy of HCC. The HCC aptamer and the EPR effect of nanoparticles, in particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 31 publications
0
16
0
1
Order By: Relevance
“…Many types of bioactive macromolecules including oligonucleotides, aptamers, antibody, , peptides, and proteins have also been used to modify CS for targeted delivery. Targeting peptides or proteins with reactive carboxylic groups could be conjugated to C2-NH 2 of CS .…”
Section: Modification Of Cs With Versatile Biofunctions For Cancer Di...mentioning
confidence: 99%
“…Many types of bioactive macromolecules including oligonucleotides, aptamers, antibody, , peptides, and proteins have also been used to modify CS for targeted delivery. Targeting peptides or proteins with reactive carboxylic groups could be conjugated to C2-NH 2 of CS .…”
Section: Modification Of Cs With Versatile Biofunctions For Cancer Di...mentioning
confidence: 99%
“…These unique physicochemical properties endow GQDs with excellent potential in tumor therapy. Chen et al ( 47 ) combined aptamer-modified GQDs with magnetic chitosan to form novel photothermal-chemotherapy drug delivery nanosystems (DOX-Fe 3 O 4 @CGA). The results of an in vivo antitumor experiment showed that under NIR laser irradiation, the temperature of the tumor site in mice increased rapidly to 43–45°C, and the tumor volume and weight significantly decreased over time.…”
Section: Classification Of Photothermal Nanomaterialsmentioning
confidence: 99%
“…Chen et al prepared an aptamer-modified GQD/chitosan nanodrug delivery system (DDS) for photothermal therapy of liver cancer, which can target hepatocellular carcinoma, significantly inhibit tumor growth in mice, and prolong the survival time of tumor-bearing mice, with good prospects for collaborative tumor treatment. 270 Yoosefian and colleagues reported a drug-delivery system using GQDs as a carrier to load the anticancer drug docetaxel (DTX). This system has good stability, and the presence of copolymers delays drug adsorption and increases the adsorption and solubility of DTX.…”
Section: Biological Applications Of Quantum Dotsmentioning
confidence: 99%